The Effect of Conflict of Interest and Lack of Innovation on Family Business Failure - Aldi Akbar Ramadhan; Ibrahim Hasan; Muhamad Delvin Azzahra; Muhamad Rizki Akbar; Mira Nurfitriya; Azizah Fauziyah (UM Purwokerto Press, 2024)
Failure in a family business can result in interpersonal tensions and serious financial problems. Factors such as lack of planning, conflicts of interest and lack of innovation can lead to such failures. The difficulty in maintaining a balance between personal and professional relationships is often a major challenge in family businesses. The purpose of this study is to identify the factors that lead to family business failure, evaluate the associated risks, and explore the recovery actions that can be taken. This research uses a quantitative method with a descriptive verification approach to collect and analyze data. The object of this research is a family business owned by a student family in Tasikmalaya. The results of this study indicate that conflicts of interest and innovation have an effect of 80.5% on the failure of family businesses owned by UPI Tasikmalaya campus students. This proves that if there is a conflict of interest and innovation in the family business that is not immediately resolved properly, the family business will fail.